Inhibition of hedgehog signaling attenuates carcinogenesis in vitro and increases necrosis of cholangiocellular carcinoma1. Issue 3 (25th January 2013) - El Khatib, Mona; Kalnytska, Anna; Palagani, Vindhya; Kossatz, Uta; Manns, Michael P.; Malek, Nisar P.; Wilkens, Ludwig; Plentz, Ruben R.
Abstract The Hedgehog signaling pathway plays a pivotal role during embryonic development, stem cell maintenance, and wound healing. Hedgehog signaling also is deregulated in many cancers. However, the role of this signaling pathway in the carcinogenesis of cholangiocarcinoma (CCC) is still unknown. In this study, we investigated the effects of Hedgehog inhibition by cyclopamine and 5E1 in cultured human CCC cell lines and in vivo using a xenograft mouse model. We also investigated the involvement of Hedgehog in epithelial to mesenchymal transition (EMT), migration, and CCC tumor growth. Sonic hedgehog (Shh) ligand was highly expressed in 89% of human CCC tissues and in CCC cell lines. Cyclopamine and 5E1 treatments effectively inhibited cell proliferation, migration, and invasion by down‐regulating the Hedgehog target genes glioblastoma 1 and glioblastoma 2. In vitro and in vivo, we detected an increase in epithelial marker, E‐cadherin, after Hedgehog inhibition. In addition, we saw an increase in necrotic areas and a decrease in mitotic figures in cyclopamine and 5E1‐treated CCC xenograft tumors. Conclusion: This study supports the presence of autocrine Hedgehog signaling in human CCC, where CCC cells produce and respond to Shh ligand. Blocking the Hedgehog pathway inhibited EMT and decreased the viability of CCC cells. In addition, cyclopamine and 5E1 inhibited the growth of CCC xenograft tumors. (HEPATOLOGY 2013)